Stress-induced Oral Lichen Planus Immunopathogenesis and Potential Therapy: A Narrative Review - Basalamah, Fatimah F.; Pramitha, Selviana R.; Pasaribu, Togu Andrie S.; Rahayu, Retno Pudji; Ayuningtyas, Nurina Febriyanti; Ernawati, Diah Savitri (Indonesian Journal of Dental Medicine, 2022)
Background: Oral lichen planus is a chronic inflammatory condition that only involves in the oral cavity and is mediated by the cellular immune system. The etiology of OLP is unclear but autoreactive T lymphocytes are considered to play an important role in the development of OLP. Factors like stress and psychological anxiety have been associated with OLP but their roles in the development of OLP is yet explored. Purpose: To describe stress-induced OLP immunopathogenesis and therapeutic potential. Reviews: In the early stages, the mechanism of OLP involves the expression of keratinocyte antigens or exposure to an antigen in the form of self-peptide or heat shock protein (HSP). HSP90 is the most expressed heat shock protein in the basal layer of keratinocytes and plays a role in recruitment of cellular immune cells through the production of cytokines due to TLR2/4 and CD91 activation, inflammatory cell migration due to 4 integrin activation, and increased antigen presentation due to HSP90-peptide binding to MHC class I/II. Stress as a physiological response triggers the release of the hormone cortisol from the adrenal cortex and catecholamine hormones such as epinephrine/ adrenaline and norepinephrine/noradrenaline from the adrenal medulla. Catecholamines increase the migration of T lymphocyte cells through the interaction of integrins and integrin ligands on the endothelium through the expression of 2-integrin after binding to adrenergic receptors on the cell membrane. Conclusion: Oral lichen planus is a chronic inflammatory condition caused by various factors where stress increases the migration of T lymphocyte cells on the side that expresses self-peptides and antigens through the interaction of immune cells with catecholamines. Topical nonselective beta blockers can be supporting therapy in reducing pain and size of OLP lesions.